Images of the past - Price, T. Douglas (McGraw-Hill, 2013)
"Images of the Past is an introduction to prehistoric archaeology that aims to capture the excitement and visual splendor of archaeology while providing insight into current research methods, interpretations, and theories in the field. To introduce our text, we offer some background on why we wrote the book, describe its organization and distinctive features, indicate what is new in this edition, provide some information on the various supplements, and, finally, acknowledge all those individuals and institutions that have contributed to Images of the Past"--